Optimizing Big Data Management on Microsoft SQL Server: Enhancing Performance through Normalization and Advanced Analytical Techniques - Altınışık, Süleyman Burak; Bilgin, Turgay Tugay (My University, 2025)
This study investigates Big Data management challenges and solutions in cable manufacturing using Microsoft SQL Server (MSSQL), focusing on performance optimization, normalization, and advanced analytical techniques. Addressing the 4Vs of Big Data, our case study collects data from 45 TAGs at one-minute intervals, generating approximately 56 million daily records. We employ OPC technology for data acquisition, strategic normalization processes, and advanced MSSQL optimization techniques. Normalization significantly reduced data redundancy, decreasing the dataset from 56 million to 283 rows per day and improving query execution times from over 40 minutes to less than 0.1 seconds for complex analytical queries. We also propose a database-independent software development approach to balance cost and performance. This research contributes practical insights into performance optimization, scalability, and cost-effective solutions for organizations managing large-scale data processing challenges in industrial settings, offering a blueprint for efficient Big Data management that balances technical performance with economic considerations.
Keywords: Big Data Management; Performance Optimization; Data Normalization; Cable Manufacturing